An inverse heat transfer method for predicting the thermal characteristics of a molten material reactor. (5th September 2016) - Hafid, Mohamed; Lacroix, Marcel
Highlights: The solid/liquid phase change of the bank is investigated. The Levenberg-Marquardt-Method combined with the Broyden-Method is deployed. The inverse method is thoroughly tested for a wide range of test cases. The characteristics and the position of the temperature sensor are examined. Abstract: An inverse heat transfer procedure is presented for predicting the time-varying thickness of the protective bank that covers the lining of the refractory brick walls of a molten material reactor. The inverse method predicts simultaneously influential thermo-physical properties of the reactor such as the thermal conductivity of the refractory brick wall, the thermal conductivity of the solid and of the liquid layers of the phase change material, and the time-varying reactor heat load. The inverse method rests on the Levenberg-Marquardt Method (LMM) combined with the Broyden method (BM). The effect (1) of the initial guesses for the unknown LMM polynomial parameters, (2) of the noise on the recorded temperature data, (3) of the location of the temperature sensors embedded into the brick wall and (4) of the number of recorded temperature data on the inverse predictions is investigated. Recommendations are then made concerning the installation and the operation of the temperature sensors.